ANALISIS PROSEDUR PEMUNGUTAN DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA BITUNG - Damanik, Crysty Hanna; Sabijono, Harijanto; Pontoh, Winston (Universitas Sam Ratulangi, 2018)
Tax is one of the biggest sources of revenue for the state. Acquisition of Land and Building Rights (BPHTB) is a source of tax revenue originally administered by the Central Government which is then transferred to Local Government which is a form of follow-up regional economic policy and fiscal decentralization. Acquisition of Land and Building Rights is one of the regional taxes which has a contribution to the revenue of the region (PAD). The BPHTB collection procedure applied in Bitung City is regulated in Mayor's Regulation Number 35 of 2014 concerning Procedures for Collection of BPHTB. The purpose of this research is to know how BPHTB collection procedure and how it contributes PAD in Bitung City. The object of this research is the Regional Tax and Retribution Agency of Bitung City. The method of analysis used in this research is descriptive qualitative method. Method of data collection is done by the process of the interview and documentation. The research result, BPHTB collection procedures in Bitung city is in compliance with Mayor's Regulation Number 35 of 2014 and the contribution BPHTB to PAD continues to increase, although every year the realization of BPHTB exceeds the target.Keywords: BPHTB, Collection Procedure,Contributions.